Does Sense of Place Still Exist? - Helena Ruotsala (Journal of Ethnology and Folkloristics)
In this article my aim is to discuss place, locality and their role and changed significance in the ethnological studies. I argue that although the meaning and role of place have been changed, place still is an important concept in ethnology. Researches are now paying more attention to the changed nature of the concept, e.g. for the multivocality of places. The anthropological literature on space and place forms my theoretical framework, with which I study some empiric cases from my familiar environment, from Finnish Lapland and from Kola Peninsula. ‘Place’, in my examples the sieidi of Taatsi, Lake Seidjavr, the Pallas fells or the tourist centre Levi, can have a unique reality for each inhabitant and visitor. While the meanings may be shared with others, the views of the place are often likely to be competing, and contested in practice. According to Margaret Rodman (2004: 207), researchers should empower place by returning control over meanings of place to the rightful producers, and empower their own analysis of place by attending to the multiplicity of local voices found about place.